Short-term outcomes of Ivor Lewis vs. McKeown esophagectomy: A meta-analysis - Xing, Huajie; Hu, Mengyu; Wang, Zhiqiang; Jiang, Yuequan (Frontiers in Surgery, 2022)
Objective: To assess the rate anastomotic leak and other perioperative outcomes among patients undergoing esophagectomy with either thoracic or cervical anastomosis. Methods: This meta-analysis was conducted by searching relevant literature in Web of Science, Cochrane Library, PubMed and Embase databases. Articles that included patients undergoing esophagectomy and compared perioperative outcomes of McKeown with Ivor Lewis procedures were included. The primary outcome parameter was anastomotic leak. Secondary outcome parameters were: grade ≥2 anastomotic leak, chylothorax, recurrent laryngeal nerve injury, hospital length of stay, ICU length of stay, postoperative mortality, operative time, blood loss, R0 resection rate, lymph nodes examined. Results: 8 studies including 3291 patients (1857 Ivor-lewis procedure and 1434 Mckeown procedure) were eligible for analysis. Meta-analysis showed Ivor-lewis procedure was associated with lower rate of all grades anastomosis leak (RR, 0.67; 95% CI, 0.55–0.82; P = 0.0001), lower rate of recurrent laryngeal nerve injury (RR, 0.14; 95%CI, 0.08-0.25), and shorter length of hospital stay (WMD, 0.13; 95%CI, 0.04-0.22). Grade≥2 anastomotic leak, chylothorax, ICU length of stay, postoperative mortality, operative time, blood loss, R0 resection rate, lymph nodes examined were similar between the 2 groups. Conclusions: This meta-analysis supports similar short-term outcomes and oncological efficacy between Ivor-lewis and Mckeown esophagectomy, though all grades anastomotic leak and recurrent laryngeal nerve injury are higher in the Mckeown procedure.